Amorphous nickel–iron hydroxide films on nickel sulfide nanoparticles for the oxygen evolution reaction. Issue 6 (25th February 2020) - He, Wenjun; Ren, Gang; Li, Ying; Jia, Dongbo; Li, Shiyun; Cheng, Jianing; Liu, Caichi; Hao, Qiuyan; Zhang, Jun; Liu, Hui
Abstract : The development of earth-abundant and low-cost electrocatalysts with high performance toward the oxygen evolution reaction (OER) plays a key role in water splitting. Abstract : The development of earth-abundant and low-cost electrocatalysts with high performance toward the oxygen evolution reaction (OER) plays a key role in water splitting. Here, a novel OER electrocatalyst of Ni–Fe–OH/Ni3 S2 nanoparticles on Ni foam (Ni–Fe–OH/Ni3 S2 /NF) was synthesized by a facile, ultrafast two-step method within 2 minutes. The obtained Ni–Fe–OH/Ni3 S2 /NF catalyst presents an excellent OER performance, only requiring a low overpotential of 268 mV to reach a current density of 10 mA cm −2 and a small Tafel slope of 54 mV dec −1 in 1 M KOH, which was sustained for 12 h at a current density of 175 mA cm −2 almost without any degradation. The superior OER performance of the Ni–Fe–OH/Ni3 S2 /NF catalyst is attributed to the increased active sites, the accelerated electron transfer between the electrode and electrolyte, and the synergistic effect between amorphous Ni–Fe–OH and Ni3 S2 . This work opens up a new avenue for preparing highly efficient heterostructure electrocatalysts toward the OER.